Generalized Quantum Key Distribution for WDM Router Applications - Djeffal, N; Benslama, M; Messaoudene, I (Review of Computer Engineering Research, 2016)
In this paper, we study the ability of quantum networks to support both random and non-random data traffic single-photon quantum communications signals on a shared infrastructure. The effect of wave length on distance coverage with the quantum bit error rate (QBER) of a quantum key distribution (QKD) system is increasing. The results of random phase showed minimal distance coverage over non-random phase. For fluctuating amplitude of random show a change in system performance improved sending capabilities. Hence, it is found that rare fluctuations should not degrade system performance significantly, but the data sending mode has a significant effect on channel integrity.